A first estimate of the effect of offshore wind farms on sedimentary organic carbon stocks in the Southern North Sea - Heinatz, Knut; Scheffold, Maike Iris Esther (Frontiers in Marine Science, 2023)
Offshore wind farms (OWFs) can increase the transfer and stock of organic carbon (OC) in the surrounding sediments during their operational phase, while their construction and decommissioning release carbon. To answer the question whether sediments of OWFs trap more OC than they release, we estimate the net carbon effect over the entire life cycle (construction, operational and decommissioning phases) of OWFs in the Southern North Sea. Based on existing studies we compare the increased OC flux due to the colonization of organisms at the foundations of wind turbines and the OC loss due to sediment-disturbing activities during construction and decommissioning. Our results show that the areal intensity of carbon release in the disturbed areas is about 43.5 times higher than that of carbon trapping in the entire area of the OWFs. However, since the disturbed areas only account for about 0.50 ± 0.06% of the total area of the OWFs, in absolute terms about 4.6 ± 1.4 times more carbon is trapped in the sediment of the OWFs than is released. Due to limited data availability and the resulting need for extensive assumptions, our estimates only represent orders of magnitude. We therefore provide sensitivity estimates that define the limits of our calculations in terms of disturbance depth, remineralisation ratio, scour protection measures and heterogenous OC contents. In addition, we identify shortcomings of our extrapolation. Further research, especially more advanced impact assessments of construction and decommissioning processes must follow to improve the understanding of impacts of OWFs on sedimentary OC.